Pericoma nielseni nom. nov., a replacement name for Pericoma formosa Nielsen, 1964, preoccupied by Pericoma formosa Meunier, 1905 (Diptera: Psychodidae) - Kvifte, Gunnar Mikalsen (Zootaxa, 2010)
Pericoma formosa Meunier, 1905 was described from Baltic amber and is of dubious systematic placement within the Psychodinae (Hennig, 1972; Meunier, 1905). Pericoma formosa Nielsen, 1964 was described from Zealand in Denmark and has later been found in Norway, France, Finland and the Czech and Slovak Republics (Ježek, 2006; Nielsen, 1964). The current work resolves the hitherto unrecognised homonymy of these names.